Effect of Distributed and Instructional Leadership of Chinese School Principals on the Job Satisfaction of Teachers: A Conceptual Paper - Xin, Zhao; Tahir, Suhaidah Binti (South Asian Journal of Social Sciences and Humanities, 2024)
School principals’ leadership behaviours influence the job satisfaction of the teacher, which in  turn, defines the effectiveness of the school climate. Therefore, it is crucial to know how the  leaderships styles, specially the distributed and instructional leadership, affect the job satisfaction  of the teachers in the Chinese school context. So, the aim of the study is to analyse the effect of  distributed and instructional leadership of Chinese school principals on the job satisfaction of  teachers along with the mediating roles of reward, motivation, and effectiveness. In order to  achieve the aim, the study adopted a “review-style” research method and explored the relevant  past literature. The researcher confined the time frame from 2019 to 2024 to include the most  recent studies and the theses, books, and discussions were not utilized as they did not fit into the  standard of research articles. In the context of educational policy and school management practices  worldwide, the implications of this study are significant. Therefore, suitable leadership  interventions would improve teachers’ work satisfaction and consequently, the students’  achievements.
Keywords: Distributed Leadership; Instructional Leadership; Principal; Teachers; Job Satisfaction